Drug resistance and genetic transmission characteristics of HIV-1 CRF59_01B in infected patients in Guangdong Province, China. (29th April 2022) - Lan, Yun; Li, Feng; Li, Linghua; Deng, Xizi; Li, Liya; Li, Junbin; Cai, Xiaoli; Ling, Xuemei; Hu, Fengyu
Abstract: Objectives: To comprehensively analyse the prevalence of drug resistance and the transmission characteristics of CRF59_01B strains in infected patients in Guangdong, China. Methods: CRF59_01B-infected individuals were recruited, and the HIV-1 pol region was amplified. Drug resistance-associated mutations (DRMs) and antiretroviral susceptibility were examined using the Stanford University HIV Drug Resistance Database to analyse pretreatment drug resistance (PDR) and acquired drug resistance (ADR). Genetic transmission networks were extracted from the maximum likelihood phylogenetic tree with Cluster Picker and visualized with Cytoscape. Results: Two hundred and twenty-five CRF59_01B-infected individuals, comprising 35 ART-experienced and 190 ART-naive individuals, were recruited. No patients harboured PI DRMs, 5.33% (12/225) of the patients harboured NRTI DRMs and 11.11% (25/225) of the patients harboured NNRTI DRMs. The overall prevalence of strains with ADR was 51.43% (18/35), while the prevalence of strains with PDR was 2.63% (5/190). A total of 20 transmission networks, involving 25.78% (58/225) database-derived sequences, were identified. The networks ranged in size from 2 to 10 individuals, of which most (55.00%, 11/20) were made up of two individuals. Among the 225 study subjects, 9.78% (22/225) had 1 link and 16.00% (36/225) had ≥2 links. Conclusions: The overall prevalence of CRF59_01B strains with ADR among the ART-experienced patients was high. Although the overall prevalence of CRF59_01B strains with PDR among the ART-naive patients was low, it is necessary to remain vigilant regarding some important DRMs.